Bail-in as an instrument protecting the banking sector from system risk vs. capital adequacy of banks in the EU - Zbigniew Kurylek (Institute of Economic Research (IER), 2017)
Research background: The article refers to the introduced bank regulations aiming at maintaining capital adequacy of banks and a stable situation in the banking sector, allowing to keep the financial system stable at a time of a possible financial or systemic crisis. Purpose of the article: This article aims at presenting methods of protecting banks. It mostly focuses on the capital structure and the use of capital assets to repay liabilities in a situation that poses a risk to the continued functioning of a banking sector or a financial system. Methodology/methods: Our research was conducted by ways of analysing literature on using bail-in in the banking sector during an ordered bank restructuring or a winding up process. Data analysis was conducted with the use of statistical methods, including correlation analysis, followed by a comparative analysis of obtained results. The level of interdependence was determined on the basis of Pearson's correlation analysis, and the results were verified with the use of J. Guildford's classification of interdependence. Findings & Value added: The article presents bail-in - an instrument aiming at performing ordered restructuring or winding up of a bank in the context of capital adequacy of banks in the European Union. The text shows how quickly and strongly capital adequacy rate of banks was changing in specific EU member states between 2006 and 2016, including the variation value evaluated with regard to the division into developed and developing countries. What is more, the article also points at current directions of changes in capital structure of banks in EU member states.
Keywords: G21; G33; 330; bail-in; financial crisis; capital adequacy